USING OF MODERN TOOLS IN THE PROCESS OF ART CREATION IN VIRTUAL REALITY - ШИМАН, К. А. (Art and Design, 2023)
The purpose of the article is to demonstrate the variety of using modern tools during artistic creation in virtual reality. Methodology. The research is based on the following methods: hermeneutic analysis, comparative analysis, system analysis, structural-functional analysis. The results. It was highlighted the contemporary artistic manifestations in virtual reality. The variety of technical tools, that artists use in practice, was considered. The main set of instruments and additional contrivances for art creation and perception were specified. The features of the involvement by artists the eye tracking system, encephalograph, spatial trackers and reading sensors was revealed. The results of its involvement were determined on the examples of the works of international (Matthew Attard, Graham Fink) and Ukrainian (Diana Faksh, Volodymyr Kovbasa, Serhij Nizhyns'kyj, Liera Polians'ka, Maks Robotov, Kateryna Shyman, Ivan Svitlychnyj) artists. The difference between the artistic realization implemented by an artist on-line in virtual reality and generative programming software creation was revealed. The consideration of art works in virtual reality on the examples let to outline the main trends of art in VR. It was indicated the principal lines of VR creative manifestations in the context of Ukrainian contemporary art. The scientific novelty consists of highlighting the implementation of modern VR tools in contemporary art. Practical significance. The results of the research are the basis for further studies and classification of artistic manifestations in VR, and for further research of the development of contemporary Ukrainian art.